In situ volcanic ash sampling and aerosol–gas analysis based on UAS technologies (AeroVolc) - S. Thivet; G. Bagheri; P. M. Kornatowski; P. M. Kornatowski; A. Fries; J. Lemus; J. Lemus; R. Simionato; R. Simionato; C. Díaz-Vecino; E. Rossi; T. Yamada; et al. (Atmospheric Measurement Techniques)
Volcanic degassing and explosive eruptions inject significant amounts of gas and ash into the atmosphere, impacting the local environment and atmospheric dynamics from local to global scales. While ground- and satellite-based remote-sensing systems are key to describing explosive volcanism and assessing associated hazards, direct in situ measurements inside volcanic clouds are not possible with these methods. This study presents an innovative approach using an unoccupied aircraft system (UAS) for (i) airborne ash sampling and (ii) measurements of aerosol and gas concentrations (AeroVolc system). Commercial instruments (DJI™ Matrice 30 UAV, Alphasense™ N3 optical particle counter, and Soarability™ Sniffer4D Mini2 multigas hardware) were combined with custom-built ash collectors and particle counters to enable a more detailed analysis of volcanic clouds. Here, we showcase the deployment of our UAS on Sakurajima (Japan) and Etna (Italy), two volcanoes known for their frequent explosive eruptions and persistent degassing activity, to demonstrate how this approach enables in situ, high-resolution sample and data collection within challenging environments. Results provide grain size distributions (GSDs), information on the occurrence of particle aggregation, and solid aerosol (PM1, PM2.5, and PM10, corresponding to solid aerosol particles with a diameter of less than 1, 2.5, and 10 µm, respectively) and gas (SO2 and CO2) concentrations. Depending on whether the UAS was operated within or below ash- and/or gas-rich clouds, different insights were gained that open up new perspectives for volcanological research. These insights include the composition, concentration, generation, dispersion, and sedimentation patterns of volcanic clouds.